Malawi Public Expenditure Review 2019 : Putting Fiscal Policy on a Sustainable Path - World Bank (World Bank, Washington, DC, 2019)
Malawi’s economic growth has historically been undermined by exogenous, climate-induced shocks, as well as economic policies and management that have often exacerbated the impact of shocks. Yet since 2017, Malawi has been enjoying a period of economic stability, with double-digit inflation tamed, and a stable exchange rate for the first time since 2011. This is the first module of a programmatic Public Expenditure Review.